Two is better than one: innovative ants overcome the nature-inspired cognitive challenge of pupal insertion - Pathak, Manish Kumar; Halder, Subhashis; Mukhopadhyay, Snigdha; Annagiri, Sumana (Frontiers in Ecology and Evolution, 2023)
The cognitive abilities of animals play a crucial role in their capacity to adapt to changing environments. Experiments to understand cognition are usually performed on animals like nonhuman primates, canids or corvids. These studies often use food as the motivating factor. However, in the current study, we used a new paradigm to investigate the ability of ponerine ants who are solitary foragers, to solve a nature-inspired problem. As pupae are the most invested brood item and are directly associated with the colony’s fitness, we designed a set-up that imposed a challenge towards transporting the pupae into the new nest for relocating colonies. We used a narrow nest entrance through which an adult could enter but rendered the passage of an adult, holding a pupa, virtually impossible. Through this, we examined the capacity of these ants to overcome the ‘pupal insertion’ challenge by investigating eight colonies, involving 425 pupal insertions, performed by 104 uniquely labelled ants. We found that 80% of all pupae were inserted by employing a novel cooperative behaviour; one ant pushing and the other ant(s), inside the nest, pulling the pupa. Even though individual ants showed high variability in their performance regarding pupal insertion, the initial three successive insertions showed significant improvement in their performance. Such improvement was also documented at the colony level, with shorter durations and fewer attempts for subsequent pupal insertions. Our study showcases that ants can overcome difficult environmental challenges through innovation and subsequently improve their performance, without training or reward.